PENDAMPINGAN MAHASISWA MBKM UIN PALANGKA RAYA DALAM KEGIATAN MUHADHARAH DI MA MIFTAHUL JANNAH - Nurlisda Nurlisda; Ali Iskandar Zulkarnain; Sri Sukaprihatin (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
This study is grounded in the importance of improving students’ public speaking skills through muhadharah activities. The research aims to describe the mentoring process conducted by MBKM students from UIN Palangka Raya in the muhadharah program at MA Miftahul Jannah and to identify its impact on students’ abilities. This study employs a descriptive qualitative method through participatory observation, interviews, and direct mentoring sessions. The findings reveal that the monthly muhadharah activities significantly enhance students’ confidence, understanding of religious material, and public speaking competence. The mentoring provided by university students supports participants in preparing materials, improving rhetorical techniques, and creating an interactive learning atmosphere. Additionally, the program benefits the mentors by strengthening their communication, classroom management, and teaching skills.